Self-Triggered Control of Multi-Agent Systems With External Disturbances - Li, Xiang; Zhu, Jing (Frontiers in Control Engineering, 2022)
This paper investigates the consensus of multi-agent systems(MASs) by virtue of event-triggered mechanism. Considering the existence of external disturbances, we use a disturbance observer to estimate the disturbance signals and eliminate the corresponding effects by using estimators to compensate the input control terms. The self-triggered condition is designed and proved that there is no Zeno behavior. We show that the proposed disturbance observer can estimate the external disturbance signals well under the self-triggered condition. Finally, simulation examples are presented to verify the theoretical results.